Acceptability and feasibility of a financial incentive intervention to improve retention in HIV care among pregnant women in Johannesburg, South Africa. Issue 4 (3rd April 2018) - Clouse, Kate; Mongwenyana, Constance; Musina, Melda; Bokaba, Dorah; Long, Lawrence; Maskew, Mhairi; Ahonkhai, Aima; Fox, Matthew P.
ABSTRACT: Women initiating antiretroviral therapy during pregnancy are at high risk of dropping out of HIV care after delivery. We assessed the acceptability and feasibility of a financial incentive – a one-time R50 (∼USD4) supermarket voucher for completing one postpartum visit ≤10 weeks of delivery – to improve postpartum retention. We enrolled 100 pregnant, HIV-positive women at a primary health clinic in Johannesburg, South Africa. Participants were interviewed at enrollment and we reviewed files to assess retention ≥14 weeks postpartum. Median (IQR) respondent age was 28 years (24–31) and 31% were employed. Most (86%) said the incentive would motivate them to return and 76% supported clinics offering incentives. Among the 23% who found the intervention unacceptable, the most frequent reason was perceived personal responsibility for health. Feasibility was demonstrated, as 79.7% (51/64) of eligible participants received a voucher. When asked to rank preferred hypothetical incentive interventions, assistance with social services ranked first (29%), followed by infant formula (22%) and cash (21%); assistance with social services was the top-ranked choice by both those who found the voucher incentive intervention acceptable and unacceptable. To encourage HIV-positive women to remain in care, respondents most frequently suggested health education (34%), counseling (29%), financial incentives (25%), home visits (13%), and better service (6%). Our results suggest financial incentives are acceptable, but women frequently expressed preference for integrated services and improved education and counseling to improve retention. Interventions exploring the feasibility and efficacy of education and counseling interventions to improve postpartum HIV care are warranted.